STRATEGI HUBUNGAN MASYARAKAT DALAM PENGELOLAAN WEBSITE SEBAGAI MEDIA INFORMASI DAN LAYANAN PUBLIK DI KEMENTERIAN AGAMA PROVINSI RIAU - Yessy Afrioza; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Regional Office of the Ministry of Religion of Riau Province is one of the government agencies that uses the website as a source of information media for the public. Management of website thiswith the domain riau.kemenag.go.id is managed by the Information and Public Relations division or the so-called Inmas. Riau Ministry of Religion has many branches under it such as the Religion of the Regency / City Department office, for that Riau Ministry of Religion uses websites as sources of information. The purpose of this research is to find out how the management process starts from the process of finding data and facts to defining the problem, planning the program, implementing the program and the final stage, namely the evaluation. A good management process will produce what the public wants so that this website becomes a media of information and public services.This research uses a qualitative method with a descriptive approach. With his subject the Head of the Head of the Head of Inmas and 5 staff of Inmas in accordance with the criteria of thetechnique purposive and his object, namely the management of the website as a medium of information and public services. Data collection techniques used were interviews, observation, and documentation.data analysis techniques Miles and Huberman. To achieve the validity of the data in this study, the authors used an extension of participation and triangulation.The results showed that in managing the website of the Ministry of Religion of Riau Province, the Public Relations of the Ministry of Religion of Riau Province determine, namely: First: The Planning and Programming Phase, at this stage Planning a program must set the targets, strategies, and tactics needed in implementing a management program. Second, Information and Public Relations Implementation Stage carries out its duties as a manager of information and public services, this can be seen in the activities in running the government website, such as making news relating to the Ministry of Religion that is there are five fields, there are five subagents, and four advisors, all conditional reporting. Third, the Evaluation Phase, at this stage sets a number of standards and measuring tools that have been previously set in the program planning process as well as estimating work performance.